Representasi Budaya Kerja Pasca Pandemi Covid-19 pada Pegawai Pascasarjana UIN Raden Intan Lampung - Zuliana, Erni (Al-Bustan: Jurnal Pendidikan Islam, 2024)
Work culture refers to a set of deeply internalized attitudes, feelings, and psychological frameworks possessed by members of an organization. Culture encompasses mental behaviors and habits that have become ingrained in individual activities and the performance outcomes of these individuals. Based on the results of data analysis regarding the representation of work culture (corporate culture) post-COVID-19 pandemic in the Graduate School environment of Raden Intan State Islamic University Lampung, five work cultures were implemented, which include: (1) Integrity, (2) Professionalism, (3) Innovation, (4) Responsibility, and (5) Exemplary Behavior. Meanwhile, the results of monitoring and evaluating the work culture post-COVID-19 pandemic for employees in the Graduate School environment of UIN Raden Intan Lampung are; (1) Organization of Administrative Affairs, (2) Organization of the human resource management system (HR) which includes; (a) Employee needs planning, (b) Competency-based employee development, (c) Individual performance determination, (d) Enforcement of discipline/code of ethics for employees. (3) Strengthening performance accountability, (4) Improving the quality of public services, (5) Enhancing the employee information system.